AN EXAMINATION OF CONSUMER PROTECTION WITH FOOD SAFETY REGULATIONS IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
This article examines the framework of consumer protection in India, focusing on the Consumer Protection Act of 1986 and the associated food safety regulations. It elucidates the pivotal role of these laws in safeguarding consumer rights, particularly in the context of food safety, and assesses the effectiveness of the mechanisms established for grievance redressal. The discussion is supplemented by relevant case law, underscoring the legal landscape that shapes consumer protection in India. The article incorporates visual aids, including tables and charts, to illustrate trends and case outcomes effectively.